Multi-media distribution, partitioning, and risks of tire additives and their transformation products in coastal waters of China - Liu, Chao; Lu, Shuang; Lv, Min; Fu, Longwen; Man, Mingsan; Du, Yize; Ding, Jing; Liu, Wei; Chen, Lingxin (Elsevier, 2026)
Tire additives and their transformation products (TATPs) are emerging as contaminants of global concern due to their widespread environmental occurrence and potential ecotoxicity. The multimedia environmental behavior of TATPs in marine systems remains poorly understood. Herein, we present the first large-scale investigation of 25 TATPs in seawater, sediment, and suspended particle matter (SPM) from the southern Bohai Sea and northern Yellow Sea of China. Twenty, 17, and 20 TATPs were detected in seawater (30.4–693 ng/L), sediment (8.41–118 ng/g), and SPM (34.6–5436 ng/L), respectively, with N,N′-Di-2-butyl- p -phenylenediamine (44PD) being the most predominant compound. Hydrophobic interactions play a key role in the partitioning of TATPs between seawater and sediment and 44PD tended to remain predominantly in the seawater. The Yellow River Estuary and inner Laizhou Bay were major contamination hotspots, primarily influenced by terrestrial inputs. Medium to high ecological risks of TATP mixture were exhibited across all seawater samples, largely attributable to 44PD. Algae were found to be more sensitive to TATP exposure compared to crustaceans and fish. With a priority index of 4.70, 44PD was identified as a high-risk pollutant requiring prioritized monitoring. These results provide valuable insights into the understanding of the environmental behavior of TATPs and the TATP management.